DEVELOPMENT OF THE ACTIVITY OF THE MUSIC AND DRAMA THEATER OF THE SYRDARYA REGION - F. N. Turgunov (Modern World Education: New Age Problems – New solutions, 2025)
This article describes the history and activities of the Syrdarya region musical drama theater, as well as the performances staged in the theater over the years, as well as the activities of the actors who played in them.